The Adaptation Test on Yardlong Bean Lines Tolerant to Aphids and High Yield - Kuswanto .; Budi Waluyo (AGRIVITA, Journal of Agricultural Science, 2011)
The adaptation trial was applied to determine the benefits of genotype-environmental interaction, adaptability and stability of lines. The previous research successfully obtained 8 UB lines which had high yield and tolerant to aphids. These lines belong to plant breeding laboratory of Brawijaya University, which had stability and a high potential can be immediately released to the public. Research was conducted in 2010, dry and rainy season, on 3 locations of yardlong bean, namely Malang, Kediri and Jombang. Randomized Block Design was applied in these locations.Genotype-environment interaction was analyzed with combined analysis of nested design.The adaptability and stability were known from regression analysis based on the stability of Eberhart and Russel. There were 6 stabile lines, namely UB7070P1, UB24089X1, UB606572, UB61318, UB7023J44, and UB715, respectively. They were recommended to be released as new varieties which had pest tolerance and high yield. The UBPU was suitable to be developed in marginal land. The 6 new varieties had registered to Agriculture Department Republic of Indonesia, namely, Brawijaya 1, Brawijaya 3, Brawijaya 4, Bagong 2, Bagong 3 dan Bagong Ungu, respectively. Keywords : adaptation, yardlong bean, stability, tolerant aphid